Performance comparison of natural refrigerants based cascade systems for ultra-low-temperature applications - Sarkar J.; Bhattacharyya S.; Lal A. (My University, 2025)
Theoretical analyses and optimisation are carried out with ethane, ethylene and nitrous oxide as the low-temperature (LT) fluids in a cascade system for ultra-low-temperature refrigeration applications to examine the effects of design and operating parameters. Finally, performance improvement has been investigated employing an internal heat exchanger. Optimal intermediate temperature (IT) correlations have been developed. Ethane is superior in terms of coefficient of performance (COP), whereas nitrous oxide is superior in terms of volumetric cooling capacity as an LT fluid. With increase in compressor efficiency, COP increases; however, with little influence on the optimum IT. Using an internal heat exchanger in the LT circuit, the cooling COP can be increased for ethane and ethylene; however, there is marginal decrease in COP for N 2O. Ammonia is not suitable as a HT fluid for some operating conditions where the optimum IT is lower than the normal boiling point and propylene may be a suitable substitute with a penalty on COP. © 2013 © 2013 Taylor & Francis.